The Use Of Synonyms and Antonyms in K.Rakhmanov’s Dramatic Works - Perijamal Turganbayeva (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2026)
This study investigates the semantic functions and stylistic significance of synonyms and antonyms in the dramatic works of Karakalpak playwright K.Rakhmanov. Through a detailed lexical-semantic analysis, the paper explores how the author utilizes synonymous and antonymous expressions to enhance character portrayal, intensify dramatic conflict, and enrich the artistic language of his plays. The research identifies various forms of synonymy, including lexical, derivative, and borrowed word pairs, and demonstrates their role in avoiding redundancy and expanding the expressive capacity of the Karakalpak language. Similarly, antonyms—derived from nouns, adjectives, and adverbs—are shown to serve as essential tools for conveying contrast, highlighting thematic oppositions, and constructing dynamic dialogues. The paper also draws on comparative insights from Turkic linguistics and Karakalpak stylistic theory to contextualize Rakhmanov’s linguistic choices within the broader framework of modern Turkic dramaturgy. The findings suggest that the systematic use of semantic contrast not only reflects the lexical richness of the language but also serves as a hallmark of Rakhmanov’s distinctive literary style and cultural engagement. This study contributes to the ongoing exploration of stylistic devices in Turkic literature and affirms the value of lexical-semantic tools in the development of national literary identity.